2015
DOI: 10.3109/08916934.2015.1037441
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 in systemic lupus erythematosus: A comprehensive review

Abstract: Systemic lupus erythematosus (SLE) is a complicated autoimmune disease of multifactorial pathoaetiology. One of the most serious manifestations is lupus nephritis. The pathogenesis of SLE has not been well elucidated, but it has been reported that interleukin-17 (IL-17) and Th17 cells play important roles in the pathogenesis of SLE. IL-17A, a member of IL-17 family, amplifies the immune response by inducing the local production of chemokines and cytokines, recruiting neutrophils and monocytes, augmenting the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 102 publications
4
75
0
1
Order By: Relevance
“…Expansion of Th17 cells has been included in a growing list of autoimmune disorders [53, 54]. Our studies, as well as those of others, have demonstrated that Th17 cells play a key role in the pathogenesis of SLE [17, 18, 54].…”
Section: Oxidative Stress and Th17 Abnormalitysupporting
confidence: 70%
See 1 more Smart Citation
“…Expansion of Th17 cells has been included in a growing list of autoimmune disorders [53, 54]. Our studies, as well as those of others, have demonstrated that Th17 cells play a key role in the pathogenesis of SLE [17, 18, 54].…”
Section: Oxidative Stress and Th17 Abnormalitysupporting
confidence: 70%
“…Expansion of Th17 cells has been included in a growing list of autoimmune disorders [53, 54]. Our studies, as well as those of others, have demonstrated that Th17 cells play a key role in the pathogenesis of SLE [17, 18, 54]. Environmental factors, including exposure to UV radiation, infection, environmental pollution, and emotional changes, are believed to contribute to the increased prevalence of SLE and to aggravate lupus activity [55].…”
Section: Oxidative Stress and Th17 Abnormalitymentioning
confidence: 61%
“…In recent years, several IL‐17A pathway inhibitors (e.g. brodalumab, ixekizumab and secukinumab) have been tested in clinical trials . More recently, IL‐17‐producing T cells have been shown to induce renal inflammation by activating neutrophils or by participating in macrophage‐mediated tissue injury .…”
Section: Introductionmentioning
confidence: 99%
“…brodalumab, ixekizumab and secukinumab) have been tested in clinical trials. [5] More recently, IL-17-producing T cells have been shown to induce renal inflammation by activating neutrophils or by participating in macrophagemediated tissue injury. [6] Furthermore, T cells and cytokines participate in proliferative glomerulonephritis as well as ischaemia reperfusion injury (IRI).…”
Section: Introductionmentioning
confidence: 99%
“…There are studies have found that the number of Th17 cells and IL‐17 levels significantly increased in SLE patients and SLE mice . IL‐17 has synergistic effect on B cell‐activating factor (BAFF), promotes B cell differentiation and autoantibody production, and induces or promotes SLE . The role of Th17 cells and their cytokines in the pathogenesis of RA has been confirmed in RA rat model and human body.…”
Section: T Cell Subsets Balance and Rheumatic Immune Diseasementioning
confidence: 93%